Estrogens, estrogen receptors and melanoma. Issue 5 (May 2011) - de Giorgi, Vincenzo; Gori, Alessia; Grazzini, Marta; Rossari, Susanna; Scarfì, Federica; Corciova, Suzanna; Verdelli, Alice; Lotti, Torello; Massi, Daniela
The skin is the largest nonreproductive target tissue on which estrogen plays many beneficial and protective roles. Although neither exogenous hormones nor pregnancy represent significant risk factors for melanoma, epidemiological data suggest a higher survival rate in women with metastatic disease versus men and in premenopausal versus postmenopausal patients. Despite the fact that hyperestrogenic signaling has long been implicated in the initiation and progression of several tumors, the role of estrogens in malignant melanoma is still unclear. The cellular effects of estrogens are mediated by two subtypes of estrogen receptors (ERs). Estrogen receptor ββ (ERββ), the predominant ER in the skin, antagonizes the proliferative action mediated by estrogen receptor αα. According to recent immunohistochemical studies, ERββ protein expression decreases progressively with increased Breslow thickness and results in more invasive melanomas; thus, ERββ immunophenotype may distinguish melanomas linked to poor prognosis from those with a favorable course and lead to melanoma unresponsiveness to both estrogen and anti-estrogen treatment. Therefore, if future large-scale immunohistochemical and molecular studies point towards ERββ as an important factor in malignant melanoma progression, they will open up novel and targeted prognostic and therapeutic perspectives.